Growth resilience to weather variation in commercial free-ranging chickens in Ethiopia - Banos, G.; Girma, Mekonnen; Solomon, Bersabhe; Davoudi, P.; Esatu, Wondmeneh; Dessie, Tadelle; Psifidi, A.; Watson, K.; Hanotte, Olivier H.; Sánchez-Molano, E. (BioMed Central, 2025)
Background: The poultry industry in sub-Saharan Africa is a rapidly developing sector mostly based on smallholder farming. Increased demand for poultry-derived products, driven by the growing economy and population, has intensified importations of highly productive exotic breeds and crossbreeding with local ecotypes. However, commercial chickens with exotic genes often struggle to adapt to the local climate under smallholder farmers management. Understanding the chicken response to weather changes is crucial for developing selection schemes that ensure proper adaptation. In the present study, we derived individual phenotypes for growth resilience of commercial free-ranging chickens to changing weather conditions in Ethiopia. In addition, we performed genomic association analyses to assess the genetic background of these phenotypes and identify potential candidate genes of interest.